The Usefulness Of Clinician Education On The Completion Of Laboratory Investigation Forms - Aliena Sohail, Sundas Ali, Shahzad Ali Jiskani, Asfa Zawar, Rabiah Asghar, Humaira Rizwan (Drugs and Cell Therapies in Hematology, 2021)
Background & Objective: Pre-analytical errors constitute majority of the laboratory errors, and inadequate filling of lab request forms is one of the major causes. In order to reduce the prevalence of such errors, pathologists must play a role in highlighting its importance by periodically educating clinicians. The main aim of this study was to determine the effectiveness of educating our clinicians on the occurrence of adequately completed laboratory investigation forms. This was done by examining the error rates of pre-and post-educational intervention. Methods and Materials: This was a quasi‑experimental study conducted at the Hospital of Pakistan Institute of Medical Sciences, Islamabad. Incoming laboratory investigation forms were audited for a period of 5 months where eight data variables were being looked into. Then clinician education took place via seminars and educational programs for 4-week duration. A repeat audit for the same data variables was carried out for another period of 5 months. SPSS version 21 was used to analyze the data. Error rate (%) was calculated as missing number of variables/ Total number of request forms reviewed*100. Chi square test was used to compare pre and post rates of error and ap < 0.05 was considered significant. Results: Error rates for missing variables pre‑and post‑clinician education were: Hospital number pre = (40.0%), post = (10.7%); Date pre = (38.1%), post = (13.5%); Patient’s Name Pre (58.2%), Post = (25.7%); Doctor’s name Pre = (79.2%), Post = (38.5%); Age pre = (77.3%), post = (38.5%); p<0.001, Gender pre = (76.0%), post = (50.7%); Clinical Notes pre = (96%), post = (77.4%); Ward/Dept. pre = (48%), post = (35.3%); p=0.03. Conclusion: Most of the investigation forms that returned to the laboratory were adequately completed. This showed that educating clinicians on proper completion of these investigations forms by using interactive media was an effective approach.